Voltage Controlled Integrator and Linear Quadrature-VCO Using MMCC - P. Venkateswaran; R. Nandi; Sagarika Das (Institute of Advanced Engineering and Science, 2013)
A Voltage Controlled Oscillator (VCO) based on the new multiplication-mode current conveyor (MMCC) building block is presented. The oscillator is realized using a double integrator loop (DIL) where a linear frequency (fo) versus the control voltage (Vc) tuning characteristics with quadrature sinusoid signal generation in a range of 40 kHz ≤ fo≤ 700 kHz had been experimentally verified. The fo─ sensitivity is low while the frequency stability factor (Sf more than 1) is high at satisfactory values of total harmonic distortion (THD ≈ 1.11%).